2003
DOI: 10.1038/sj.mp.4001203
|View full text |Cite
|
Sign up to set email alerts
|

HLA and genetic susceptibility to sleepwalking

Abstract: HLA-DQB1 typing was performed in 60 Caucasian subjects with sleepwalking (SW) disorder and their families and 60 ethnically matched subjects without any diagnosed sleep disorder. A total of 21 sleepwalkers (35.0%) were DQB1*0501 positive vs eight (13.3%) controls (P ¼ 0.0056; odds ratio ¼ 3.5, 95% CI ¼ 1.4-8.7). The family data for all HLA subtypes were further assessed for allelic association with SW using the transmission-disequilibrium test. A significant excess transmission was observed for DQB1*05 and *04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
14

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(86 citation statements)
references
References 19 publications
2
70
0
14
Order By: Relevance
“…9 Prevalence appears unaffected by gender or socio-economic status, but has a genetic basis. 10,11 Various drugs, most recently Zolpidem, 12 have been reported to be associated with sleepwalking but this is controversial, being based on small numbers of cases and often without thorough investigation of alternative causation. 13 Among those who exhibit sleep walking, an episode can follow sleep deprivation.…”
Section: Somnambulismmentioning
confidence: 99%
“…9 Prevalence appears unaffected by gender or socio-economic status, but has a genetic basis. 10,11 Various drugs, most recently Zolpidem, 12 have been reported to be associated with sleepwalking but this is controversial, being based on small numbers of cases and often without thorough investigation of alternative causation. 13 Among those who exhibit sleep walking, an episode can follow sleep deprivation.…”
Section: Somnambulismmentioning
confidence: 99%
“…In a recent study on 60 Caucasian subjects and their families we reported a positive association between the HLA-DQB1*05 subtype and sleepwalking [82]. The frequency of DQB1*0501 was increased in sleepwalking patients while DQB1*0602 (associated with narcolepsy) was slightly decreased.…”
Section: Sleepwalking and Night Terrorsmentioning
confidence: 99%
“…Tal dissociação implica, por exemplo, na presença de atividade motora típica da vigília, durante estado de sono eletrograficamente determinado. Existem fatores genéticos 20,21,22 e ambientais relacionados, podendo os ataques serem desencadeados por febre, álcool, privação de sono, stress emocional (Tabela II). Além destes, qualquer distúrbio do sono capaz de induzir à fragmentação do sono, favorecendo, portanto, à dissociação das variáveis fisioló-gicas, pode potencialmente provocar tais parassonias.…”
Section: -Parassoniasunclassified